Vareniklin: bezpečná léčba závislosti na tabáku u kardiovaskulárních pacientů - Kmeťová, Alexandra; Zvolská, Kamila; Králíková, Eva (Casopis lekaru ceskych, 2014)
Smoking is the leading risk factor for cardiovascular (CV) diseases. Eliminating exposure to tobacco smoke reduces CV risk in half. Tobacco dependence is similar to heroin addiction in its mechanisms and level of addictiveness or treatment success. Treatment includes both a change of daily stereotypes and pharmacotherapy. The most effective medication, varenicline, which depending on intensity of intervention triples the success rate, has been used since 2006, in the Czech Republic since 2007. It is a pity that its wider application is limited by the fear of its side effects; though it would be difficult to find a comparable risk of smoking with any drug. Papers describing this association were not methodologically correct and this relationship was also refused by the recent Cochrane Review publication - increased cardiovascular risk in connection with varenicline was not proved. Because the negative reports have been highly publicized, we consider to be useful to bring the overview, from which it is recognizable that varenicline is safe in terms of CV risks.
Keywords: kardiovaskulární nemoci; vareniklin; Humans; benzazepiny; chování snižující riziko; poruchy vyvolané užíváním tabáku; rizikové faktory; Risk Reduction Behavior; nikotinoví agonisté; Benzazepines; Nicotinic Agonists; lidé; odvykání kouření; Smoking Cessation; Cardiovascular Diseases; Tobacco Use Disorder; Quinoxalines; Varenicline; Smoking; kouření; chinoxaliny; Risk Factors